WEDC Technical Brief No. 20: Water sampling - Len Hutton (2025)
The objective of water sampling. This technical brief describes the sampling procedures for bacteriological testing of water (see Technical Brief No. 18, Water testing, for details of the analysis) The objective of water sampling is to collect and deliver for analysis a sample of water representative of the bulk of water being examined. Sampling procedures are as important as the analysis. Care needs to be taken to ensure that there is no accidental contamination of the sample during sampling and transport. Bacteriological analysis results are used to check the quality of treated drinking-water at taps and standposts on a distribution system. The other major use is to evaluate contamination by faecal bacteria of water sources, such as springs, boreholes, rivers and lakes.